The diagnostic dilemma of sinusoidal-type primary hepatic angiosarcoma: A case report and literature review - Dong, Linfei; Xu, Jinghang; Wang, Ke; Liu, Hui; Liang, Li; Ma, Huimin; Wang, Yan; Huo, Na (Frontiers in Oncology, 2025)
BackgroundPrimary hepatic angiosarcoma (PHA) is a rare, highly aggressive, and rapid progressive malignant liver tumor, of which the sinusoidal growth pattern represents one of its uncommon morphological subtypes. Nonspecific clinical presentation, absence of characteristic laboratory findings, and variable imaging features often contribute to diagnostic delays. As a result, patients often miss the window for potential treatment interventions. This study aimed to deepen the understanding of the imaging characteristics of PHA in order to enhance the sensitivity of clinical doctors in identifying rare tumors.Case summaryA 75-year-old woman presented with poor appetite and progressive jaundice. Initial imaging studies conducted 4 months before admission did not raise strong suspicion for a rare malignant lesion, which contributed to a prolonged viewing time and subsequently led to the decision to perform a liver biopsy. Eventually, immunohistochemical staining of the percutaneous liver biopsy confirmed the diagnosis of sinusoidal-type PHA. Due to her poor baseline condition and critical status, the patient lost the opportunity to receive antitumor treatment and succumbed to the disease within 2 months of diagnosis.ConclusionThis case underscores the challenges in the early imaging detection of PHA and emphasizes the need for heightened clinical vigilance toward rare liver malignancies. Although histopathology remains the diagnostic gold standard, earlier recognition of suggestive imaging features may prompt a more timely biopsy, enabling prompt treatment and potentially improving outcomes.